HUBUNGAN PANJANG-BERAT DAN FAKTOR KONDISI IKAN CUPANG SERBAN MALEM ENDEMIK (Betta rubra PERUGIA 1893) DI KANAL AIR PERBUKITAN MALEM, KABUPATEN ACEH JAYA, PROVINSI ACEH, INDONESIA - Fazril Saputra; Zulfadhli Zulfadhli; Muhammad Arif Nasution; Ahmad Fahrul Syarif; Maftuch Maftuch; Friyuanita Friyuanita (Jurnal Perikanan Unram, 2024)
The serban malem fish (Betta rubra) is an endemic to fresh waters. This fish is spread across the western and southern regions of Aceh Province. One of the distribution locations for this fish is the Malem Hills water canal, Aceh Jaya Regency, Aceh Province. This research aims to determine the growth patterns and condition factors of the serban malem fish found in the water canals of the Malem Hills, Aceh Jaya Regency, Aceh Province. The research location was determined using a survey method based on previous research and information from local residents. The purposive sampling method was used to collect fish samples. Sampling was carried out from August to October 2023. During the research, 138 fish samples were obtained consisting of 91 male fish and 47 female fish. The total body length of the fish ranges from 2.1-5.0 cm, and the weight of the fish varies from 0.05-0.91 grams. The results showed that the growth patterns of males and females were negatively allometric, with condition factors ranging from 0.5071-to 1.8846.